Knowledge, attitude, and practice of probiotics for oral health among dental students: A cross-sectional study - Lakshmi Krishnan; Saravanan Poorni; M S Nivedhitha; Manali Ramakrishnan Srinivasan (Wolters Kluwer Medknow Publications, 2022)
Background: Over the years, probiotics have emerged as successful supplements for oral care management. Despite their extensive benefits and uses, their application in dental care is less due to limited knowledge about them among dentists. Aim: This study aimed to assess the knowledge, attitude, and practice in using probiotics for oral health among dental students of Chennai city. Materials and Methods: A cross-sectional online survey was conducted among 209 dental students through Google Forms. Pretested questionnaire with 14 close-ended questions was used. Ethical clearance and consent were obtained before the study. Statistical test was computed using SPSS version 20, and P value was kept at < 0.05 for significance. Results: Majority of the participants (86%) were aware of the probiotics and its use, but hardly 19% of them had put their knowledge into practice. A statistically significant difference was obtained between the male and female participants with the knowledge domain of the questionnaire (P = 0.021*, 0.006*, 0.048*). Conclusion: From the present study, we can conclude that the participants were well aware of the term probiotics but hesitated to prescribe it to their patients as their awareness of the availability of probiotics was less.